Yth. Editor, Service Quality Fisioterapi : Studi Deskriptif Di RS PKU ‘Aisyiyah Kendal: Service Quality Fisioterapi : Studi Deskriptif Di RS PKU ‘Aisyiyah Kendal - Fahmi Rizal; Sigit Prasojo; Dzikra Nur Septiani (Jurnal Riset Teknologi Kesehatan, 2026)
Hospitals as a level of advanced service after the Community Health Center are highly demanded to provide maximum and best services. Services in the health sector have a serious impact on the sustainability of a service in order to maintain competition. Physiotherapy is part of the health service efforts owned by a hospital. The purpose of this study is to analyze the quality of service, especially in the Physiotherapy service unit. This study is a type of quantitative research with a descriptive observational method at one time (cross sectional). The population of this study were new patients in the Physiotherapy Unit of PKU 'Aisyiyah Kendal Hospital, the sample obtained was 70 people with the determination using Accidental sampling. The results of this study found that the quality of service in the Physiotherapy unit of PKU 'Aisyiyah Kendal Hospital is dominated by good perceptions. Physical evidence (tangible) 68.57%, Reliability 65.71%, Responsiveness, Assurance 61.43%, Empathy 64.29%.